Nature and landscape sustainability in Portuguese rural areas: Which role for farming external benefits valorisation? - Lívia Madureira (European Regional Science Association (ERSA), 2004)
Traditional farming systems are declining rapidly in Portugal. These labour intensive and low productivity systems are incompatible with depopulation and ageing of rural areas. This lack of socio-economic sustainability endangers nature and landscape conservation. Agri-environmental measures, applied in European Union since 1994, can be seen as potential answer to that problem in the Portuguese case. But to be effective, these measures need to be part of an integrated strategy directed to mitigate depopulation. The NGOs and the official organisations related to nature and landscape conservation are aware of that and acknowledge it in the National Strategy for Nature and Biodiversity Conservation. This decline in the farming external benefits supply happens simultaneously with the increasing of its demand. General public, of all ages and socio-economic strata, wants rural nature and landscape conservation for use and nonuse purposes. Contingent Valuation studies conducted in the North of Portugal (Santos, 1997; Madureira, 2001) show a positive willingness to pay of visitors and general public to assure traditional agrarian landscape conservation. To preserve the rural cultural heritage is the main reason presented by the public to stand for landscape maintenance. Official data on land use and demographic trends, data on touristic demand for rural areas and empirical evidence on public preferences for rural nature and landscape attributes are used to witness these different directions in supply and demand for farming external benefits. A closer look to this divergence is taken for the case of Trás-os-Montes e Alto Douro. This Region contains various typical landscapes where farmer's action shaped nature in a singular way. This feature attracts many tourists and visitants, which number is expected to grow, specially for Douro vineyards classified as Humanity Patrimony. But all of these landscapes are, to a more or less extent, risking being abandon or restructured to allow mechanisation. Afforestation it is also becoming an alternative pattern in soil occupation at the Region. Thus, this Region exemplifies very well the social and political choices that come up in the context presented in this communication: (1) Which landscapes to preserve? How much of it? And (2) How to do it? Use Beneficiary Pays Principle or Provider Gets based mechanisms? The first questions are mainly social issues, making evident the importance of getting information on public preferences for related political decisions. The second group asks for political choices, where the main challenge is to define and implement solutions capable of tuning in societal choices with local population and economic agents aspirations and resources. Without these solutions traditional landscape will disappear. Some face that as inevitability. But should it be so? The general public seems to disagree with that. And increasing touristic demand indicates opportunities for local development through farming external benefits valorisation. Bringing evidence and discussion on these questions is the main purpose of this communication.
Keywords: 330